Environmental and Social Sustainability in UK Construction Industry: a Systematic Literature Review - Misopoulos, Fotios; Manthou, Vicky; Michaelides, Zenon; Adebayo, Ayomide (European Journal of Economics and Business Studies, 2019)
Research on sustainability in the construction industry is common in construction journals addressing the potential adverse effects conventional practices have in the construction community. Sustainability is addressed through the environmental, social and economic impacts in literature and researchers and practitioners always drive the need for an equal attention on these three dimensions, but not so successfully at present. Sustainability covers a broad content with various suggested approaches arising from different countries all over the world. Previous studies have investigated sustainable construction issues as a global concept and in individual developed countries such as the US, Australia, and China. The aim of this research is to investigate the extent of coverage, by academia, of the sustainability concept in UK construction industry, with a focus on the environmental and social aspects of sustainability, based on the Triple Bottom Line framework. The researchers conducted a systematic literature review, searching relevant articles with predefined criteria in two major bibliographical databases, which offer great coverage of the existing academic journals in social sciences. The study utilised the PRISMA reporting approach and the search resulted in thirty-one suitable articles. The findings revealed that environmental sustainability receives much more attention than social sustainability. Added emphasis is given to green buildings and materials used. Government regulations seem to be the leading driver for adopting sustainable practices, while lack of knowledge/awareness of sustainable best practices is the leading challenge.